2013
DOI: 10.1159/000357447
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bevacizumab for Radiation-Induced Cerebral Necrosis in Children

Abstract: Introduction: Bevacizumab has been reported to effectively reduce cerebral edema caused by radiation therapy. However, only limited data with a short follow-up in tumor patients are available so far. Patients and Methods: Two children suffering from hemorrhage from arteriovenous malformation (AVM) have been treated with stereotactic radiotherapy and developed radiation-induced cerebral edema with deteriorating neurological status despite maximized steroid therapy. Bevacizumab administration at 5 mg/kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…42,43 There are also anecdotal reports on the use of bevacizumab in subjects with brain AVMs. 4448 However, efficacy and safety of this therapy in human brain AVMs remain to be determined, and a phase I trial is currently enrolling adult patients with high-grade AVMs (NCT02314377). Our findings suggest the possibility to use anti-Shh treatments as novel therapeutic approach for brain AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 There are also anecdotal reports on the use of bevacizumab in subjects with brain AVMs. 4448 However, efficacy and safety of this therapy in human brain AVMs remain to be determined, and a phase I trial is currently enrolling adult patients with high-grade AVMs (NCT02314377). Our findings suggest the possibility to use anti-Shh treatments as novel therapeutic approach for brain AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al [12] reported improvement in symptoms – including reduction of headaches and increased strength – and a reduction in T2 FLAIR. Preuss et al [13] supplied examples of using bevacizumab in pediatric patients with mixed results. Both the patients experienced marked reduction in T2 FLAIR but with only initial symptom improvement that proved marginal long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Other options include hyperbaric oxygen therapy 19 or bevacizumab, a vascular endothelial growth factor (VEGF)-A inhibitor, in addition to steroids. [20][21][22] In children, bevacizumab can improve serial neurological examinations and permit weaning of corticosteroid therapy in most patients but carries a small risk of serious adverse events. 20,23 Currently, there is insufficient evidence to guide the comparative effectiveness of these alternative therapies.…”
Section: Cerebral Edema and Radionecrosismentioning
confidence: 99%
“…Children are prone to significant complications from prolonged corticosteroid use, including Cushingoid features, weight gain, hypertension, insomnia, avascular necrosis, and stunted growth. Other options include hyperbaric oxygen therapy 19 or bevacizumab, a vascular endothelial growth factor (VEGF)‐A inhibitor, in addition to steroids 20‐22 . In children, bevacizumab can improve serial neurological examinations and permit weaning of corticosteroid therapy in most patients but carries a small risk of serious adverse events 20,23 .…”
Section: Brainmentioning
confidence: 99%